2021
DOI: 10.1021/acs.jmedchem.0c01468
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 3-(4-(2-((1H-Indol-5-yl)amino)-5-fluoropyrimidin-4-yl)-1H-pyrazol-1-yl)propanenitrile Derivatives as Selective TYK2 Inhibitors for the Treatment of Inflammatory Bowel Disease

Abstract: TYK2 mediates signaling of IL-23, IL-12, and Type I IFN-driven responses that are critical in immune-mediated diseases. Herein, we report the design, synthesis, and structure−activity relationships (SARs) of 3-(4-(2-((1H-indol-5-yl)amino)-5fluoropyrimidin-4-yl)-1H-pyrazol-1-yl)propanenitrile derivatives as selective TYK2 inhibitors. Among them, compound 14l exhibited acceptable TYK2 inhibition with an IC 50 value of 9 nM, showed satisfactory selectivity characteristics over the other three homologous JAK kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…In our previous research, we designed the selective TYK2 inhibitor 14l, which had a low in vivo bioavailability of 11.9% and did not show a significant effect on the treatment of inflammatory disease compared to tofacitinib. 36 The analysis of compound 14l showed that the cyano end and the electron-rich bicyclic ring system might be the reasons for the metabolic instability. Therefore, we considered to replace the cyano group and modify the bicyclic ring.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous research, we designed the selective TYK2 inhibitor 14l, which had a low in vivo bioavailability of 11.9% and did not show a significant effect on the treatment of inflammatory disease compared to tofacitinib. 36 The analysis of compound 14l showed that the cyano end and the electron-rich bicyclic ring system might be the reasons for the metabolic instability. Therefore, we considered to replace the cyano group and modify the bicyclic ring.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Considering the advantages of JAK1/TYK2 in inflammation, we tried to design and synthesize new dual-target inhibitors. In our previous research, we designed the selective TYK2 inhibitor 14l , which had a low in vivo bioavailability of 11.9% and did not show a significant effect on the treatment of inflammatory disease compared to tofacitinib . The analysis of compound 14l showed that the cyano end and the electron-rich bicyclic ring system might be the reasons for the metabolic instability.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, anti-TNF-α biologics may exhibit serious side effects, including infection, cancer, and death. Therefore, identifying effective and safe inflammatory targets and developing corresponding drugs is an urgent task for treatment of IBD. …”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC), emerging as a public health challenge worldwide, is an idiopathic chronic inflammatory bowel disease (IBD) causing bloody diarrhea and inflammatory alterations . The incidence and prevalence of ulcerative colitis have been increasing over time worldwide. , Recently, clinical statistics showed that some UC patients could progress toward major dysplasia of the intestinal glands, and ultimately toward malignant states such as carcinogenesis and cancer. , Various types of drugs have been used for the treatment of UC depending on the severity and the extent of the disease, such as 5-aminosalicylic acid (ASA), corticosteroids, immunomodulators, calcineurin agents, and biologics. , Among the biologics, anti-TNF-α agents are well studied and extensively used in moderate-to-severe UC patients. Unfortunately, the disadvantages coming from these antibodies are also obvious. In addition to the high cost and requirement of intravenous injection, such treatment could elicit an autoimmune response, potentially weakening patients’ immune defense. , Therefore, small-molecule drugs may serve as better alternatives in this case to modulate tumor necrosis factor α (TNF-α) production .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Various types of drugs have been used for the treatment of UC depending on the severity and the extent of the disease, such as 5-aminosalicylic acid (ASA), corticosteroids, immunomodulators, calcineurin agents, and biologics. 6,7 Among the biologics, anti-TNF-α agents are well studied and extensively used in moderate-to-severe UC patients. 8−10 Unfortunately, the disadvantages coming from these antibodies are also obvious.…”
Section: Introductionmentioning
confidence: 99%